Combretastatins D series and analogues: from isolation, synthetic challenges and biological activities - Lima Neto, Jorge de; Menezes, Paulo Henrique (Beilstein Journal of Organic Chemistry, 2023)
The combretastatin D series and its analogues, corniculatolides and isocorniculatolides belong to a class of macrocycles called cyclic diaryl ether heptanoids (DAEH). This review is intended to highlight the structure elucidation, biosynthesis, and biological activity of these compounds as well as the use of different strategies for their synthesis.
Keywords: combretastatin D; corniculatolide; isocorniculatolide; macrocycles